Access to plant genetics resources for food and agriculture and benefit sharing in China: legal framework, current practices and future developments - Xiaoyong Zhang (Wiley, 2012)
The International Treaty on Plant Genetic Resources for Food and Agriculture is the only legally binding international instrument that governs the conservation, sustainable use, access and benefit‐sharing of plant genetic resources for food and agriculture (PGRFA). The Treaty plays a particularly vital role in ensuring sustainable agricultural development and food security. Since its entry into force, much progress has been made in implementing the Treaty. China has not yet acceded to the Treaty even though it holds a large number of accessions. Against this background, this article introduces China's legal framework that regulates access to PGRFA and benefit‐sharing as well as current practices for access to PGRFA and benefit‐sharing in China. It recommends China's accession to the Treaty following necessary amendments to the existing legal system.